PERKEMBANGAN KEADAAN JALAN HUTAN MENURUT WAKTU DAN HUBUNGANNYA DENGAN POTENSI EROSI TANAH - Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1990)
An  investigation of  the  development  of  forest  road  condition in relation to soil  erosion  potential  was carried  out at  four logging  companies in  South Kalimantan in 1989  to  find  the potential of forest roads in erosion processes  after constructed and  continually    used, or abandoned  for various years. The condition of road elements especially those  related to factors stated  in the  Universal Soil Loss Equation were recorded  and, based on this information, the category of specific roads in erosion potentials was decided  subjectively  to either  one of very small,  small, medium, rather large, and  large. From  the results,  the following conclusions may  be withdrawn:In general, erosion potentials of  forest roads is decreased  with  time  due  to the growth  of various vegetation  and the process  of  natural soil stabilization.For  continually used main  roads, erosion potentials after about 2  years  are still  rather  large to large; after 3-6 years  are medium; and  beyond 6 yers are very small to small.  If main roads are totally abandoned, erosion potentials after left around one year are rather  large; after  2-3 years are small to medium; and  beyond  3 years are very small.For branch roads, erosion potentials for those abandoned up to one year are rather large to  large; abandoned 2 - 3 years  are medium to rather large; beyond 3 years are very small  to small. For skidding roads that  constructed by clearing  vegetation only or  vegetation, litter and  top  soils  all  together,  when  abandoned one  year or more, they  were densely couered by vegetation and for litter and,  therefore,   their erosion potentials   are very small  to small. Erosion  potential tendency for skidding  roads constructed by soil  cutting  and filling  is almost  the same as that  in branch roads.Logging company practices outside Java showed that they are  lacking  in  the  knowledge   of  soil  erosion,  soil stability, drainage  structures,   and  using  vegetation   for  covering  soil surfaces, all  of  which  are important  in minimizing environmental disturbances   due  to road construction activities.